Designing e-procurement applications for procurement of goods and web-based services at PT. Prima International Cargo - Lili Kurniawan; Cahyani Budihartanti (Journal of Information System, Informatics and Computing, 2022)
Procurement is the activity of procuring goods and services including procurement of goods, procurement of construction works, procurement of private consultancy services and provision of other services. Therefore the importance of the supply system in a business so that all activities or processes can be recorded and easier, therefore at PT. Prima International Cargo started using the E-Procurement application to make it easier in all processes, because previously the procurement or purchase process for certain goods or services was not yet computerized properly. This is due to my lack of knowledge about computer systems. Computers support businesses to store data easily and quickly. Simple and clear data storage levels make it easy to find the data you ordered. Currently, almost all types of businesses have implemented a computerized system. The E-Procurement application is based on a website so that it can be accessed by the procurement party to carry out the process at any time. This application is also made with the PHP programming language, the Codeigniter framework, and the mysql database system, using apache as the web server.